Comparison Of Isotonic Beverage And Mineral Water Consumption On Archery Score And Hydration Status Of Archery UKM Athletes At State University Of Surabaya - Syifa' Itmi'nanil Qolbi; Satwika Arya Pratama; Cleonara Yanuar Dini; Ratna Candra Dewi (International Journal of Health Engineering and Technology, 2026)
Archery is a precision sport that requires high concentration and postural stability, so hydration status may potentially affect athlete performance. This study aimed to compare the effects of isotonic drink and mineral water consumption on archery scores and hydration status, as measured by urine specific gravity (USG), among archery athletes of Universitas Negeri Surabaya. This quasi-experimental study used a crossover design involving 20 active athletes who received both interventions alternately. Fluid was administered at 150 mL every 10 minutes during the training and scoring sessions, with a total volume of 1,050 mL. Archery performance was assessed using the World Archery Federation scoring sheet, while hydration status was measured using USG reagent strips. Data were analyzed using the Wilcoxon Signed Rank Test. Results showed no significant difference in archery scores between mineral water and isotonic drink consumption (p=0.070). Isotonic drink significantly decreased USG (p=0.001), while mineral water did not (p=0.088). However, the change in USG between the two interventions also did not differ significantly (p=0.062). It is concluded that there were no significant differences in archery scores or in hydration status change between mineral water and isotonic drink consumption. Nevertheless, isotonic drink consumption showed a significant decrease in urine specific gravity within its own group.